Power Quality Improvement on Wind Energy System by Using STATCOM - Farah Atiqah, Ali Yusup; Shirley, Rufus; Prashobh, Karunakaran; Nazreen, Junaidi; Nurul 'Izzati, Hashim (Trans Tech Publications Ltd., 2016)
Wind energy known as a cheap, clean and uncontrolled resource and becomes an important green electricity source. However, installation of wind system into an electric grid introduces the Power Quality (PQ) phenomenon. These poses great challenges leads to various control schemes and new techniques to mitigate the PQ events. This paper described the improvement of PQ events in a grid connected wind energy system by using Static Compensator (STATCOM) with a Battery Energy Storage System (BESS) at the Point of Common Coupling (PCC). The performance of the proposed wind energy system is simulated via MATLAB/SIMULINK in power system block set.